COMPARATIVE STUDY OF VARIOUS GASTRORETENTIVE APPROACHES - Supriya Mor, Mansi Gulati* Anupama Diwan (Journal of Pharmaceutical Research and Opinion, 2014)
Present study is aimed to evaluate the influence of polymer content and polymer type on the release profile of drug. In this invention, gastroretentive controlled release platform was developed based on three approaches that is raft, matrix based on KollidonSR and Xanthum gum and Bigranular approach.. All these approaches used sodium bicarbonate as the gas generating medium for creating the buoyancy that led to gastric retention. Ciprofloxacin Hydrochloride has been selected as model drug. It is highly water soluble drug with an absorption window at upper jejunum with dose of 598.47 mg. Out of the three approaches tried, even with low compression forces tablets of astonishing hardness has been obtained with Kollidon SR and Xanthum gum matrix based approach. Even results of biphasic gastro retentive delivery was also satisfactory, but, raft approach was not proved its stance to the extent of matrix based approach. The time of flotation was 620 min. and the drug release was sustained for 18 hrs and hence the optimized systemic control of 24 hrs with matrix based GR approach. Drug loading was achieved to be more than 60%. Polymer to drug ratio was achieved with lowest possible content of 16-17%. The Kollidon SR and Xanthum gum matrix based approach could prove to be the best among the three approaches tried.